Reliability and conditional diagnosability of hyper bijective connection networks. Issue 1 (2nd January 2020) - Lian, Guanqin; Zhou, Shuming; Cheng, Eddie; Liu, Jiafei; Chen, Gaolin; Gu, Zhendong
Abstract : The g -extra connectivity and diagonalisability are two important metrics to fault-tolerance and robustness of a multiprocessor system whose network structure is modelled by a graph. In this work, we explore the reliability of a newly proposed network called hyper bijective connection networks (HBC, for short), which is an extension of the family of the well-known interconnection networks, such as hypercube and its variants. We prove that 2-extra vertex connectivity and 3-extra vertex connectivity of n -dimensional HBC are 3 n + m −6 for m ≥ 3 and n ≥ 4 and 4 n + m −8 for m ≥ 4 and n ≥ 4, respectively. Using its desirable fault-tolerance, we show that the conditional diagonalizabilities of n -dimensional HBC under the PMC model are m + 4 n −7 (resp., 4 n −5) for m ≥ 4 and n ≥ 4 (resp., m = 3 and n ≥ 4 ) and its conditional diagonalizability under MM ∗ model is m + 3 n −6 for m ≥ 3 and n ≥ 4 .